Effects of a morphine-rabbit anti-morphine antibody mixture on guinea-pig isolated ileum - Bleiberg, M. J. (1973)
Incubates of morphine with serum globulins obtained from sera of rabbits immunized with a morphine-bovine serum albumin conjugate produced immediate Schultz-Dale contractions when added to superfused, electrically stimulated guinea-pig ileal strips. Incubates of morphine with Krebs-Henseleit solution produced relaxation and depression of tone, and inhibition of electrically induced contractions. It is concluded that the spasm of guinea-pig ileum produced by incubates containing morphine-binding serum globulins and morphine resulted from transient passive sensitization and an acute anaphylactic type of response.